Pengaruh Model Pembelajaran Project Based Learning terhadap Kemampuan Menulis Cerita Rakyat Kelas V SD Negeri O6 Ladang Padi - Fitri Zulva Hasanah; Otang Kurniaman; Munjiatun Munjiatun (Universitas Maritim AMNI Semarang, 2025)
This study aims to describe the effect of the Project Based Learning model on the ability to write folk tales among fifth-grade elementary school students. The method used is a quasi-experimental design with a nonequivalent control group design. The subjects of this study were fifth-grade students of SD Negeri 06 Ladang Padi. The sample consisted of two classes: class VA as the experimental group and class VB as the control group. The experimental class implemented the Project Based Learning model, while the control class used a text-based teaching method. The students' ability to write folk tales was measured through a pretest and posttest administered to both groups using the same question, consisting of one item. The statistical data analyzed included normality tests, homogeneity tests, and hypothesis testing, processed using SPSS 23 software. The results showed that the hypothesis test produced a significance value of 0.00 < 0.05, indicating that Ha was accepted and Ho was rejected.The influence of the Project Based Learning model can be seen in the significant improvement in the experimental class. The improvement in students' ability to write folk tales was evidenced by the difference in the average posttest scores between the experimental and control classes. The experimental class achieved an average posttest score of 80.13, while the control class scored 60.12 on average. These findings demonstrate that the implementation of the Project Based Learning model significantly affects the ability to write folk tales among fifth-grade students at SD Negeri 06 Ladang Padi.